Leadership in early education in times of change : research from five continents - Strehmel, Petra; Heikka, Johanna; Hujala, Eeva, 1950-; Rodd, Jillian; Waniganayake, Manjula (Research monograph (International Leadership Research Forum Early Education) ;, 2019)
The collection brings together the latest work of researchers from Australia, Africa, Asia, and Europe focusing on early childhood leadership matters. It covers different aspects of leadership in early education: professional education and development, identity and leadership strategies as well as governance and leadership under different frame conditions.